1988
DOI: 10.1172/jci113399
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Na-K-ATPase activity in the mouse medullary thick ascending limb of Henle. Effects of mineralocorticoids and sodium.

Abstract: This study investigates the effect of variations in mineralocorticoid as well as cell sodium delivery and uptake on Na-KATPase activity in the mouse medullary thick ascending limb of Henle (mTALH). Pharmacologic doses of the mineralocorticoid deoxycorticosterone acetate (DOCA) resulted in a 28% increase of Na-K-ATPase activity. Furosemide-induced inhibition of sodium uptake by the mTALH cell also resulted in Na-K-ATPase activity reduction (45%). Sodium deprivation did not cause a clear change in enzyme activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Several studies in both mTAL and collecting duct have demonstrated that chronic reductions in apical sodium entry can diminish basolateral Na/K-ATPase activity in the presence of aldosterone stimulation (21)(22)(23). For example, in mTAL, Grossman and Hebert (21 ) demonstrated that mineralocorticoid-induced increases in pump activity could be prevented by chronic inhibition of the apical cotransporter using furosemide. Similarly, in collecting duct, chronic amiloride inhibition of apical sodium channels blocks mineralocorticoid stimulation of Na/ K-ATPase (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in both mTAL and collecting duct have demonstrated that chronic reductions in apical sodium entry can diminish basolateral Na/K-ATPase activity in the presence of aldosterone stimulation (21)(22)(23). For example, in mTAL, Grossman and Hebert (21 ) demonstrated that mineralocorticoid-induced increases in pump activity could be prevented by chronic inhibition of the apical cotransporter using furosemide. Similarly, in collecting duct, chronic amiloride inhibition of apical sodium channels blocks mineralocorticoid stimulation of Na/ K-ATPase (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…No other correlation was found between con-pellets have been accepted as a reliable method of adtinuous variables. Leaking (bursting location) occurred ministering drugs continuously for long periods of time in the preanastomotic segment of the colon in all but [8,9]. The perioperative administration (6 weeks preone specimen in the steroid group, and in this rat leak-operatively and 8 or 12 days postoperatively) approxiage occurred at the anastomosis.…”
Section: Respectively After Pellet Insertion and Were Excludedmentioning
confidence: 99%
“…Related studies have also focused on the effects of a chronic increase in salt delivery to the loop. Feeding rats a high-salt diet for 5 d leads to an increase in the relative abundance of both the apical NaK2Cl transporter and an increase in the basolateral Na,K-ATPase ␣1 (30); the increase in TALH Na,K-ATPase activity can be prevented by treating rats with the NaK2Cl inhibitor furosemide (31,32), evidence for a causal link between chronic salt delivery to the TALH stimulating increased apical transport (by NaK2Cl) and driving an increase in basolateral sodium pump activity. Is there any adaptive rationale for an animal on a high-salt diet to reabsorb more salt in the loop of Henle?…”
Section: Discussionmentioning
confidence: 99%